Evaluation of 3D cognitive fatigue using heart-brain synchronization - Park, Sangin; Won, Myoung Ju; Lee, Eui Chul; Mun, Sungchul; Park, Min-Chul; Whang, Mincheol (ELSEVIER, 2015)
The purpose of this study was to identify an evaluation method for 3D cognitive fatigue based on a heart-brain synchronization phenomenon known as the heartbeat evoked potential CHEF). Thirty undergraduate students (15 females) watched a video in both 2D and 3D for an hour. Because visual fatigue is related to cognitive load, the HEP was used as an indicator of communication between the heart and the brain and therefore of cognitive function; responses were compared after 2D and 3D viewing. At the standard EEG sites F3 and F4, the alpha activity of the first and second HEP components was significantly increased after 3D video viewing relative to 2D. This increase likely indicates that sensory input from 3D video requires heavy computation by the brain, stimulating heart activity. The conclusion is that the first and second HEP components are significant parameters that can quantitatively evaluate 3D visual fatigue. Further work is needed to uncover the cause of 3D visual fatigue. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: MENTAL FATIGUE; CARDIAC AWARENESS; VISUAL FATIGUE; LCD TV; POTENTIALS; EYESTRAIN; COMPONENT; P300; PERFORMANCE; CONVERGENT